Diffusion and Adoption of Oat NARC Variety in Rainfed Area, Pakistan - Naheed , Sobia; Habib, Nusrat; Anwer, M Zubair; Siddiqui, Sabeen (Asian Journal of Agriculture and Rural Development, 2014)
The present study was planned to estimate the extent of diffusion (spread) and adoption of fodder variety Oat NARC developed by Fodder Programe NARC. For this study, farm level information was collected through a formal survey method. For the official survey, an organized and well-structured questionnaire was designed. Mainly oat area of Pothwar region was the study domain. Overall from all selected tehsils, 65 farmers were taken as sample farmers. The findings of present study that includes frequency, descriptive analysis, oat adoption rate and also identified adopters and non adopters. Technical, extension, financial, agro-colmatic and marketing factors constraining adoption of Oat NARC variety also acknowledged. Main objective of this study is to determine the factors affecting the adoption of Oat NARC variety through probit model. Factors like fodder area, soil type, cultivated land , nearest grain market (distance in km), farming experience (years), present level of involvement in farming, availability of credit for purchasing inputs, different varieties you have tested at your farm have positive role in the adoption of Oat NARC variety. The above mentioned variables positively affecting the adoption of oat NARC. This model also show that the area wheat, input market (distance in km), area for local variety, distance from market, lack of knowledge of market information and do you prefer change of varieties grown affects the adoption of Oat negatively.